HUBUNGAN PENGETAHUAN DENGAN SIKAP IBU TENTANG IMUNISASI HEPATITIS B PADA BAYI (0-11 BULAN) - Arifah Septiane Mukti (Universitas Galuh, 2019)
Hepatitis B infection is a public health problem in the world. In Indonesia every year there are 36% of infants who have not received immunization, so in 5 years there are 2 million children who have not received hepatitis B immunization. Many factors cause people to be reluctant to immunize their babies, one of which is predisposing factors namely knowledge. This study aims to find out the relationship between the level of knowledge of mothers about hepatitis B immunization and the attitude of mothers to immunize their babies in the work area of Panumbangan Health Center, Panumbangan District. The study design used a field survey that was correlated with a cross-sectional approach. The sample is 84 respondents of mothers who have 1-year babies. The sampling technique used in this study is stratified random sampling. The level of knowledge of mothers about the notion of hepatitis B immunization is at most low categories 37 (44.0%) respondents. The attitude of mothers to believe their babies to the Puskesmas was the most negative attitude 46 (54.8%) respondents. There is a relationship between a mother's knowledge about hepatitis B immunization and the attitude of mothers to immunize their babies in Panumbangan Subdistrict (value p = 0.029 <? = 0.05). The conclusion of this study is the level of knowledge of mothers about hepatitis B immunization-related to the attitude of immunizing their babies in the work area of Panumbangan District Health Center.Keywords: Knowledge, Attitude, Hepatitis B Immunization